Revitalizing the Interior of Ndalem Puspowijoto as a Laweyan Batik Shop and Museum in Surakarta. - Yosafat Adi Pradipta; Raden Ersnathan Budi Prasetyo (Pendhapa, 2020)
Revitalizing the Interior of Ndalem Puspowijoto as a Batik Shop and Museum in Laweyan Surakarta is an effort to preserve cultural heritage buildings. The revitalization aims to maintain the building and as a means of education about batik and local wisdom of Laweyan village for the visitors and general public who care about batik. The design process is carried out using Kurtz programming including the orientation stage, the base program stage, interative programming, and design as feedback. The design approach uses the Art Deco style with the theme of Parang Saudagar. The results of the revitalization are in the form of the museum that can be used for educational purposes, and Laweyan Batik shop which has a place that is comfortable, safe, and able to accommodate the needs of both managers and visitors. The facilities consist of a lobby, café, deposit counter, shop, ticketing room, digital audio education, main display, fabric display, item display, maintenance room, multipurpose room, pantry, toilet, office, and prayer room.